2007
DOI: 10.1007/s00406-007-0757-8
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the NMDA receptor in the treatment of schizophrenia: focused on the glycine site

Abstract: N-methyl-D-aspartate receptor (NMDAR) hypo-function theory of schizophrenia proposes that impairment in NMDAR function be associated with the pathophysiology of schizophrenia and suggests that enhancement of the receptor function may produce efficacy for schizophrenia. Consistent with this theory, for the last decade, clinical trials have demonstrated that the enhancement of NMDAR function by potentiating the glycine site of the receptor is efficacious in the treatment of schizophrenia. Full agonists of the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 113 publications
2
58
0
4
Order By: Relevance
“…Post mortem studies show loss of specific GABAergic inhibitory neurons, 68 reduction in the GABA synthesizing enzyme (GAD 67 ) 69 -72 , and compensatory upregulation of the GABA A receptor 73,74 in brains of schizophrenia patients. In addition, hypofunction of the ionotropic glutamate NMDA receptor 75 and its modification 76 may play an important role in the pathophysiology and treatment of negative symptoms, respectively, and lead to inhibition of GABAergic interneurons. 77 GABA plays a key role in the function of the prefrontal cortex, an area impaired in schizophrenia 78 and linked to negative symptoms and cognitive impairment, 79,80 including working memory, a core cognitive deficit in the illness.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Post mortem studies show loss of specific GABAergic inhibitory neurons, 68 reduction in the GABA synthesizing enzyme (GAD 67 ) 69 -72 , and compensatory upregulation of the GABA A receptor 73,74 in brains of schizophrenia patients. In addition, hypofunction of the ionotropic glutamate NMDA receptor 75 and its modification 76 may play an important role in the pathophysiology and treatment of negative symptoms, respectively, and lead to inhibition of GABAergic interneurons. 77 GABA plays a key role in the function of the prefrontal cortex, an area impaired in schizophrenia 78 and linked to negative symptoms and cognitive impairment, 79,80 including working memory, a core cognitive deficit in the illness.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The recognition that NMDA inhibitor-induced behavioral effects closely mimic the symptoms of schizophrenia (Luby et al, 1959;Javitt and Zukin, 1991) engendered the hypothesis that NMDA receptor dysfunction may be a causative factor in the disease (Olney et al, 1999;Krystal et al, 2002;Tsai and Coyle, 2002;Yamada et al, 2005;Javitt, 2007;Morita et al, 2007). This hypothesis directly led to the idea that NMDA receptor potentiation may have therapeutic benefit (Heresco-Levy, 2000), a strategy explored in clinical trials of agonists at the glycine site on the NMDA receptor ( Coyle and Tsai, 2004;Shim et al, 2008;Labrie and Roder, 2010). A meta-analysis of seven small studies of glycine and D-serine as adjuncts to first-line therapy antipsychotics found evidence for a moderate reduction of negative symptoms and a trend toward a decrease in cognitive symptoms but no evidence for a beneficial effect on positive symptoms (Tuominen et al, 2005).…”
Section: F N-methyl-d-aspartate Receptor Potentiationmentioning
confidence: 99%
“…Se sabe que la cicloserina es un modulador agonista de los receptores ionotrópicos de glutamato tipo NMDA. Estos receptores, de constitución tetramérica, con dos subunidades a las que se unen moléculas de glutamato y dos subunidades a las que se adhieren moléculas de glicina consideradas moduladores alostéricos, median la neurotransmisión excitatoria al permitir la entrada de cationes (sobre todo Ca 2+ ) al espacio intracelular (Figura 1), donde se desencadenan luego intrincados procesos enzimáticos y de transcripción proteica, en áreas cruciales del sistema nervioso central (8,9). La cicloserina se une al sitio de ligazón de la glicina, aunque su agonismo es parcial y equivalente solo a entre 40 y 60% de la actividad intrínseca de la glicina, y su afinidad por el sitio receptor es entre seis a veinte veces menor (10).…”
Section: Discussionunclassified
“…Debe acotarse además que, por ser la cicloserina un agonista parcial, a bajas concentraciones obviamente ejercerá un efecto agonista, pero a altas concentraciones, al desplazar competitivamente a la glicina que posee mayor actividad agonista intrínseca, acabaría convirtiéndose en un franco antagonista (8,9).…”
Section: Correspondenciaunclassified